Thai-ness in Food Presentation: A study of International Tourists’ Perspectives - Insuwanno, Patthawee (Journal of International Studies, Prince of Songkla University, 2024)
The study explored the intricate relationship between food and culture, where food serves as a reflection of culture while culture shapes food production and presentation. This investigation focused on the perceptions of international tourists on Thai-ness elements on food presentation, examining key attributes: perceived quality (encompassing freshness, taste, and hygiene), perceived authenticity, perceived value-added, perceived food aesthetics, willingness to pay a premium, and overall satisfaction. To conduct this examination, a sensory evaluation method, the paired comparison test, was employed to determine which of two food samples exhibited superior sensory attributes. The study employed Thai cuisine, featuring two distinct presentations— one imbued with Thai cultural elements (Thai-ness), and the other without such influence (non-Thai-ness). The findings revealed that the incorporation of Thai cultural elements significantly enhanced perceptions of all tested attributes. Moreover, it unveiled that international tourists have greater willingness to pay a premium for culturally enriched food presentations. In conclusion, this study sheds light on the symbiotic relationship between food and culture, demonstrating the positive impact of cultural elements, such as Thai-ness, on food perception and international tourist’s behavior. The paper concludes with a discussion of the study’s implications and limitations, offering insights into the broader significance of this research.